2007
DOI: 10.1210/jc.2006-1393
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Body Composition in Women over Six Years at Midlife: Ovarian and Chronological Aging

Abstract: Both time (chronological aging) and ovarian aging contributed to substantial changes in body composition (fat and skeletal muscle mass) and waist circumference. These changes have important ramifications for establishing a metabolic environment that can be healthy or unhealthy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
289
4
12

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 406 publications
(323 citation statements)
references
References 29 publications
18
289
4
12
Order By: Relevance
“…Contrary to our hypothesis, we found that the rate of change in waist circumference was not significantly different during the stages of the menopausal transition among white women, while black women in the sample exhibited a slower rate of change in waist circumference after menopause. These findings are consistent with data from prior clinical studies 1, 30. Sowers et al noted an increase in waist circumference the year after the final menstrual period followed by a stabilization (or even decrease) in waist circumference 30.…”
Section: Discussionsupporting
confidence: 91%
“…Contrary to our hypothesis, we found that the rate of change in waist circumference was not significantly different during the stages of the menopausal transition among white women, while black women in the sample exhibited a slower rate of change in waist circumference after menopause. These findings are consistent with data from prior clinical studies 1, 30. Sowers et al noted an increase in waist circumference the year after the final menstrual period followed by a stabilization (or even decrease) in waist circumference 30.…”
Section: Discussionsupporting
confidence: 91%
“…At the age of ∼50 years, body weight and waist circumference increase in females. In addition, lean body mass and skeletal muscle mass decrease and fat mass increases (Ho et al 2010;Sowers et al 2007;Sternfeld et al 2004). As the time after the menopause increases, the increases in fat mass and body weight become greater (Guo et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…These somatic changes and the general ageing processes of the body together lead to changes in lifestyle (e.g. decreasing physical activity during leisure time) and quality of life [29,31,[43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…However the biological processes that lead to changes in body fat distribution during the menopausal transition, i.e., an increase of total and central body fat (in particular an increase in the accumulation of intra-abdominal fat) and a redistribution of fat from lower body subcutaneous fat toward the abdominal region [29][30][31] have not been fully explored [32,33]. In addition, the changes in body fat distribution by age and during the menopausal transition cannot be studied independently (the increase in relative body fat mass and the increase in abdominal fat accumulation are the main features of body fatness redistribution by ageing) [29,[34][35][36].…”
Section: Introductionmentioning
confidence: 99%